(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
ABSTRACT The purpose of this study was to find out the extent of government participation to empower the community in the canal environment in the jongaya village, tamalate district, Makassar city. This study used phenomenology with a qualitative research type that wqs explaining government participation in community empowerment in the canal environment in the jongaya village, the tamalate district, the city of Makassar. The total number of research informants was 3 people, m from the village office, the community around the jongaya canal area. Research information was collected through observation, interviews and documentation. The results showed there were several stages in the stages of government participation in community empowerment in the canal environment in the jongaya village, tamalate district, the city of Makassar. Keyword: Participation, In Empowerment, Channels, Local Government